Potential use of variety and crop rotation as tools for agricultural sustainability - AL-Sheikh, Abdullah, author; Barbarick, Ken, advisor; Delgado, Jorge, advisor (Colorado State University. Libraries, 2003)
Since it has been reported that NUE for potatoes {Solarium tuberosum L.) are lower than those of small grains (such as wheat (Triticum aestivum L.) or barley (Hordeum vulgare L.) and that the potential for wind erosion for potato systems, which leave small quantities of crop residue after harvest, is higher than those for small grains, we studied the potential to use potato varieties to increase NUE and crop rotations to protect soil and water quality. These studies were conducted at Colorado State University and in the San Luis Valley (SLV) of South Central Colorado. Physiological parameters such as rate of N uptake was more important for smaller rooted potato varieties while morphological parameters such as root surface area and length were more important for varieties with larger rooting systems. The Nutrient Efficiency Ratio (g tuber/g N uptake) of 277 for Norkota-Line 8 was higher than the 246 for Nugget (P <0.05). The Norkota-Line 8 was more efficient in using a unit of N to produce a unit of yield. Although Norkota-Line 8 had a smaller root surface area it was a more efficient variety and had a higher N recovery and N removal (N harvested in tubers) from the field than Nugget. Higher tuber production can contribute to reduce N losses to the environment and increase NUE. Mean crop C residue returned to the soil reduced wind erosion and was also correlated with the percentage of silt and clay (r2=0.99; P < 0.01). Crop residue returned to the soil was also positively correlated with the SOM-C (r2=0.99; P < 0.01) and SOM-N content (r2=0.99; P < 0.01). When we added about 2.5 t C ha-1 y-1 with the small grain crop residue we increased the level of SOM for these coarse sandy soils. There is potential to use cropping systems and varieties as universal tools to increase recoveries of N and conserve water quality by sequestering N in the soil organic matter, thereby reducing N losses to the environment, reducing erosion and increasing agricultural sustainability.
Keywords: soil sciences; agronomy